Determinants of Community Welfare in West Sulawesi Province Panel Data - Lubis, Firsty Ramadhona Amalia; Sukarniati, Lestari (Optimum: Jurnal Ekonomi dan Pembangunan, 2022)
The Human Development Index (HDI) is designated as one of the primary measures included in the basic pattern of regional development. This study aims to examine government spending on health, education, public facilities & housing on HDI. The data used is secondary data consisting of 2016-2020 in 6 districts/cities of West Sulawesi. The analysis method used is Fixed Effect. The results showed that government spending in the education sector had a positive and significant effect on HDI, while government spending on housing and public facilities had a significant and negative effect.